UPAYA PEMASARAN BATIK INDONESIA KE JEPANG DI ERA PERSAINGAN PASAR BEBAS TAHUN 2017-2020 - Harisatun Niswah; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Export is the sale of a commodity to another country with conditions that have been adjusted to the wishes and tastes of buyers in the export target market. Indonesia and Japan are increasingly marked by the cooperative relationship between the two countries in the economic field, namely batik exports. The Indonesian government is at the forefront of efforts to market batik to Japan. This research theoretically uses qualitative research methods. Then the theory of competitive advantage is in accordance with Porter’s indicators (Porter’s Diamond Model). Batik product are an important factor for Indonesia in trade between Indonesia and Japan. The competitive advantage is known as the industry’s national competitive advantage. Given the above background, the author uses the concept of competition policy where the policy encourages the encouragement of economic resouces throught a healty market mechanism. As for the research results from this thesis, the efforts made in country in marketing its commodities to Japan are in accordance with Porter’s theory of competitive advantage, namely factor conditions, demand conditions, related ad supporting industries, firm strategy, structure and rivalry. Indonesian batik product have a competitive advantage with the government’s role and opportunity, namely the role of the Indonesian government in an effort to increase the value of Indonesian batik exports to Japan. In an effort to increase Japanese people’s interest in Indonesian batik. The Indonesian government was able to carry out the assessment despite experiencing several challenges and obstacles. Keywords: Indonesian Batik, Competitive Advantage, Free Market